2003
DOI: 10.1007/s00414-003-0403-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fibronectin and tenascin as a demonstration of vital reaction in rat skin and muscle

Abstract: The efficiency of immunohistochemical techniques for the diagnosis of vitality of wounds decreases for lesions occurring fairly close to death. We analyzed the expression of fibronectin (FN) and tenascin (TN) in wounds inflicted in abdominal skin of 12 adult rats. An incised injury was made at 5, 10 or 15 min before death and another at 5 min after sacrifice, and collected after 45 min. Formalin-fixed paraffin-embedded sections from a total of 36 samples (mean 1.5 per wound) were immunostained following the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…Immunohistochemical studies on macrophage phenotypes (Betz et al 1995), fibronectin and tenascin (Ortiz-Rey et al 2003), and cytochemical analysis of mast cells (Bonelli et al 2003) have been performed. The accurate interpretation of bruises is essential at autopsy, and it is also considered that aging of bruises is an important component of many child abuse assessments.…”
Section: Introductionmentioning
confidence: 78%
“…Immunohistochemical studies on macrophage phenotypes (Betz et al 1995), fibronectin and tenascin (Ortiz-Rey et al 2003), and cytochemical analysis of mast cells (Bonelli et al 2003) have been performed. The accurate interpretation of bruises is essential at autopsy, and it is also considered that aging of bruises is an important component of many child abuse assessments.…”
Section: Introductionmentioning
confidence: 78%
“…By histochemistry, the expression of vascular endothelial growth factor was found to be significantly increased above baseline only after more than 12 h upon wounding in humans [21], so it seems to be of little use for shorter survival times. The expression of fibronectin and tenascin in the dermis may be of help at early time points (15 min or more) in the rat [26], but only fibronectin appears to be of help for humans at similar time points, although with limitations in terms of sensitivity and pattern of staining [27,28]. Tenascin, on the contrary, may give information only for survival times of at least a couple of days [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that since certain reactions do not occur in postmortem wounds, while in life there is a complex and organized sequence of events linked to tissue repair and restoration of the function of injured organs, making it possible to characterize, step by step, morphological and functional stages, and enabling the creation of a model that could be applied to many problems in legal or forensic medicine (Oehmichen and Kirchner 1996;Ortiz-Rey et al, 2002, 2003Oehmichen, 2004;Kondo, 2007).…”
Section: Introductionmentioning
confidence: 99%